Pengaruh word of mouth terhadap keputusan pembelian di Smile With Vegas Pekanbaru - Fiky Pramono; Annisa Mardatillah (Pelantar Press, 2022)
This study aims to see the effect of Word of Mouth on purchasing decisions in Pekanbaru. This study uses the technique of Accidental Sampling with a sample determination of 100 respondents. The data in this study were obtained through questionnaires, and the data analysis used was simple regression analysis with the spss 25.0 application for windows. This study uses simple regression analysis. The results of this study indicate that Word of Mouth has a significant influence on purchasing decisions at Smile With Vegas Pekanbaru. It can be seen that the monitoring and instrument indicators have a minimum value, while the speaker indicator has a maximum value. The average results of respondents' responses regarding purchasing decisions are classified as agree in making purchasing decisions at Smile With Vegas Pekanbaru.